Development of a breast cancer case management information platform (BC-CMIP) module based on patient-perceived value - Liang, Yinyin; Gao, Yan; Yin, Guobing; Chen, Wenjun; Gan, Xiuni (Frontiers in Oncology, 2022)
Objective To construct a content module for a breast cancer case management information platform (BC-CMIP) based on patient-perceived value (PPV). Methods A questionnaire was used to investigate the service needs of breast cancer patients and their families for the information platform. Based on the value dimensions of PPV, the module content of the BC-CMIP was initially constructed, and the Delphi method was used to justify and revise the module content. Excel 2019 and SPSS 26.0 were used for statistical analysis. Results The information platform includes the patient side and the medical side. The index content includes four primary indicators: functional value, emotional value, efficiency value and social value; it can realize all patient case management needs, such as diagnosis and treatment services, health education, telemedicine, treatment tracking, psychological support, case assessment and positive warning. Conclusion Based on the PPV, the module design of the BC-CMIP is reasonable and comprehensive, and it can scientifically and effectively meet the health needs of patients and provide a theoretical basis for subsequent platform development and application.